THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON ORGANIZATIONAL COMMITMENT OF TEACHERS AT SMP ISLAM AL-IHSAN TANGERANG SELATAN - Muhammad Aditya Putra (BAIK Publishers, 2025)
The purpose of this research is to determine the emotional intelligence on organizational commitment of teachers at SMP Islam Al-Ihsan Tangerang Selatan. The research method used in this research is descriptive with a quantitative approach. The sampling technique used saturated samples so that the number of samples in this study was 60 respondents. Data analysis technique using multiple regression. The research results show that: There is a positive and significant influence of the emotional intelligence variable on organizational commitment of teachers at SMP Islam Al-Ihsan Tangerang Selatan. This is proven by the value of tcount > ttable, namely 6.104 > 2.002 with a probability value (significance) = 0.000, which is below 0.05.